THE INFLUENCE OF BTS AS A BRAND AMBASSADOR, BRAND IMAGE, AND PRODUCT QUALITY ON PURCHASE INTENTION OF SAMSUNG GALAXY SMARTPHONES IN LHOKSEUMAWE CITY - Tsania Adilla Putri; M. Subhan; Naufal Bachri; Siti Maimunah (RADJA PUBLIKA, 2025)
This research aims to determine the influence of Brand Ambassador, Brand Image, and Product Quality on Purchase Intention of Samsung Galaxy Smartphones in Lhokseumawe City. The method used in sampling is Non-Probability Sampling, with a Purposive Sampling technique, with a total of 110 respondents. Primary data in this research was taken by questionnaires and observations. The data analysis technique used is Multiple Linear Regression Analysis Method, Classic Assumption Test, Instrument Test (Validity and Reliability), and hypothesis testing using SPSS 25.0 program. The results of this test show partially that, the brand ambassador variable (X1) has a positive and significant effect on purchase intention (Y), the brand image variable (X2) does not have a significant effect on purchase intention (Y), and the product quality variable (X3) has a positive and significant effect on purchase intention (Y). The managerial implications in this research show that improving the Brand Ambassador, Brand Image, and Product Quality will enhance the purchase intention for Samsung Galaxy Smartphones. Samsung Galaxy smartphones should continue to leverage these variables to further increase consumer interest.